Survey of basic life support knowledge in security officer of the company along The Daendles Highway - Istiroha Istiroha; Ahmad Hasan Basri (Journal of Community Empowerment for Health, 2019)
Giving first aid to traffic accident victims are often not carried out by medical personnel or competent people. The first helper in traffic accidents on the Daendles Highway is the neighboring community and security officers. The purpose of this study was to describe the knowledge level of security officers concerning basic life support in order to give first aid for the accidents along the Daendles Highway of Manyar Subdistrict, Gresik. This study used a descriptive design with a cross-sectional approach. The respondents in this study were 45 security officers of the company, which is spread along the Daendles Highway of Manyar Subdistrict, Gresik, East Java. The sample was taken by purposive sampling. Data were taken using questionnaires then analyzed by univariate techniques with SPSS 16. The results showed that security with good knowledge was 31.11%, sufficient knowledge was 55.56%, and insufficient knowledge was 13.33%. The characteristic group of respondents who had good knowledge was aged 26-35 years with a working period of 1-5 years and > 5 years, while the characteristics of the respondents who had insufficient knowledge were aged 36-45 years with a working period of 1-5 years and> 5 years. Increasing knowledge and skill about basic life support are needed to reduce mortality and increase the life expectancy of victims while waiting for help from medical personnel.